2022
DOI: 10.1016/j.fsigen.2022.102662
|View full text |Cite
|
Sign up to set email alerts
|

The application of the skin virome for human identification

Abstract: The use of skin virome offers a unique approach for human identification purposes in instances where a viable and statistically relevant human DNA profile is unavailable. The skin virome may act as an alternative DNA profile and/or an additional form of probative genetic material. To date, no study has attempted to investigate the human virome over a time series across various physical locations of the body to identify its diagnostic potential as a tool for human identification. For this study, we set out to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…The microbiomes on skin, saliva, vaginal fluid, and stool samples have been compared [ 575 ]. The stability, diversity, and individualization of the human skin virome was explored with 59 viral biomarkers being found that differed across the 42 individuals studied [ 576 ]. It will be interesting to see what the future holds and what other findings come from this active area of research.…”
Section: Emerging Technologies Research Studies and Other Topicsmentioning
confidence: 99%
“…The microbiomes on skin, saliva, vaginal fluid, and stool samples have been compared [ 575 ]. The stability, diversity, and individualization of the human skin virome was explored with 59 viral biomarkers being found that differed across the 42 individuals studied [ 576 ]. It will be interesting to see what the future holds and what other findings come from this active area of research.…”
Section: Emerging Technologies Research Studies and Other Topicsmentioning
confidence: 99%
“…We previously studied the diversity and stability of DNA viruses on human skin by sampling three anatomical locations, i.e., left hand, right hand, and scalp, longitudinally over a 6-month period for 43 human subjects ( 5 ). Briefly, samples were collected using a tandem dry and wet swab technique.…”
Section: Announcementmentioning
confidence: 99%
“…The libraries were then sequenced as 150-bp paired-end reads on the HiSeq 2500 platform (Illumina, Inc., San Diego, CA, USA). We identified one participant with a metagenome that consistently showed the presence of a feline papillomavirus, who self-identified as being an owner of a domesticated house cat ( 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…In a previous study we addressed the diversity and stability of DNA viruses on human skin by sampling three anatomical locations -left hand, right hand, and scalp -over a longitudinal 6-month period for 43 human subjects (5). Briefly, samples were collected using a tandem dry and wet swab technique.…”
Section: Announcementmentioning
confidence: 99%
“…The libraries were then sequenced as 150 bp paired-end reads on the Illumina HiSeq 2500 platform (Illumina, Inc, San Diego, CA, USA). During that study (5), we identified one participant with a metagenome which consistently showed the presence of a feline papillomavirus and who also self-identified as being an owner of a domesticated house cat.…”
Section: Announcementmentioning
confidence: 99%